Automatic Income Tax Refunds to Relieve Low Incomes - Tobias Hauck; Luisa Wallossek (Wirtschaftsdienst)
Abstract Germany is one of more than 30 countries worldwide where employees are exempt from the obligation of filing a tax return. While this optional assessment relieves one of the burden of filing a return, it has individual and distributional costs because non-filers often pay too much income tax. This excess withholding leads to considerable deviations of the effective tax burden from the tax schedule, especially in low-income brackets and particularly for employees with gross wages below the basic allowance. The resulting additional tax revenue amounted to at least 949 million euro in 2014 alone. An automatic refund of this excess withholding would especially relieve low incomes.